Theory of integral acoustoelasticity for 3-D stress-strained state - Chekurin, V. (Фізико-математичне моделювання та інформаційні технології, 2010)
Starting with the model of small elastic disturbance in a non-uniformly strained body and taking into account the weakness of the body’s acoustical inhomogeneity and anisotropy induced by strain, a theory for integral acoustoelasticity has been developed in the paper. The theory establishes mathematical models for interaction of narrow longitudinally and transversally polarized ultrasonic beams with 3-D strain field in the body. Ray integrals of acoustoelasticity have been established with the use of the model. These relationships connect measured phase parameters of longitudinally and transversally polarized ultrasonic beams, crossing the body in any direction, with integrals of initial strain distribution along this direction. They can be used to formulate problems for tomography of the body’s stress-strained state. Виходячи з моделі малого пружного збурення в неоднорідно деформованому тілі та беручи до уваги слабкість акустичних неоднорідності й анізотропії, індукованих деформацією, розроблено теорію інтегральної акустопружності. Сформульовані моделі взаємодії вузьких поляризованих ультразвукових пучків із тривимірним полем деформації у твердому тілі. У рамках моделей отримані інтегральні співвідношення акустопружності, що пов’язують зміни фаз коливань і стану поляризації поздовжньо та поперечно поляризованих ультразвукових хвиль, які пройшли через деформоване середовище, з інтегралами від розподілів компонент тензора початкової деформації вздовж напрямку поширення хвиль. Їх можна використати для формулювання задач обчислювальної томографії напружено-деформованого стану твердих тіл. Исходя из модели малого упругого возмущения в неоднородно деформированном теле и принимая во внимание, что индуцированные деформацией акустические неоднородность и анизотропия являются слабыми, разработана теория интегральной акустоупругости. Сформулированы математические модели взаимодействия узких поляризованных ультразвуковых пучков с трехмерным полем деформации в твердом теле. В рамках моделей получены лучевые интегралы акустоупругости — соотношения, устанавливающие аналитическую связь между изменениями фаз колебаний и состояния поляризации продольно и поперечно поляризованных волн, прошедших через деформированную среду, с линейными интегралами от распределений компонент начальных деформаций на направлениях распространения волн. Их можно использовать для постановки задач вычислительной томографии напряженно-деформированного состояния твердых тел.